Dealing with Taiwan - Hanns Günther Hilpert; Alexandra Sakaki; Gudrun Wacker (Stiftung Wissenschaft und Politik (SWP), 2022)
The de facto politically independent Taiwan is coming under increasing pressure from the People's Republic of China (PRC) and its claim to reunification. In addition to militarily threatening gestures, Beijing is employing economic and political means as well as cyberattacks and disinformation campaigns. This threatens the stability and status quo in the Taiwan Strait. Taiwan is of immense importance to East Asia's geopolitical dynamics: geo-strategically as part of the first island chain that restricts the PRC's access to the Pacific, and economically-technologically as a leading manufacturer of semiconductors. In the global systemic conflict between liberal-democratic and authoritarian political systems, Taiwan holds a prominent position as a consolidated, pluralistic democracy and political counter-model to the authoritarian system of the PRC. It is in the interest of Germany and Europe that peace and stability in the Taiwan Strait are preserved, to make better use of Taiwan's economic and technological potential and to extend value-based support for its free and democratic society. Germany is committed to a one-China policy, which rules out any diplomatic recognition of Taiwan. Nevertheless, there is scope to expand and intensify relations below this threshold and thus counter China's policy of intimidating and isolating Taiwan. The Taiwan policies of the United States, Japan, Singapore, South Korea, Australia, India as well as European partner countries show that there is room for pursuing closer relations with Taiwan while at the same time adhering to a one-China policy. Thus, options for action exist in foreign and security policy, trade and economic policy, as well as cultural policy.
Keywords: 320; Taiwan Strait; China; United States; Japan; Singapore; South Korea; Australia; India; East Asia; geopolitical dynamics; cyberattacks; one-China policy